PENGARUH GAYA KEPEMIMPINAN DAN KOMPENSASI TERHADAP KINERJA KARYAWAN PADA PT BUMI MAROS SEJAHTERA (PERSERODA MAROS) - Zhafran, Alif; Sahabuddin, Romansyah; Natsir, Uhud Darmawan (Bussman Journal : Indonesian Journal of Business and Management, 2024)
This study aims to determine the effect of leadership style and compensation on employee performance at PT Bumi Maros Sejahtera (Perseroda Maros). This research variable consists of Leadership Style and Compensation as independent variables and Employee Performance as the dependent variable. This type of research is quantitative associative in nature. The population in this study amounted to 34 employees of PT Bumi Maros Sejahtera (Perseroda Maros). The sampling technique used was saturated sampling with a sample size of 34 respondents. The data collection technique was carried out by distributing questionnaires to employees. Data analysis techniques using multiple linear regression with the help of SPSS version 27 software. The results of this study indicate that leadership style and compensation have a positive and significant effect on employee performance at PT Bumi Maros Sejahtera (Perseroda Maros).